Appendicitis in cystic fibrosis. Issue 3 (March 1991) - Shields, M D; Levison, H; Reisman, J J; Durie, P R; Canny, G J
Abstract : Appendicitis is said to be uncommon and difficult to diagnose in cystic fibrosis. The clinical and radiological features in nine patients with cystic fibrosis who had appendicitis were studied. All but one of the patients had an appendiceal abscess at surgery. Four patients had a delay in diagnosis of greater than three days before the correct diagnosis was made. This delay may have been due to a more indolent presentation or because these patients were initially considered to have distal intestinal obstruction syndrome. Appendicitis should be considered in the differential diagnosis if a contrast enema demonstrates extrinsic compression of the caecum. Ultrasound, computed tomography, and gallium scans were found to be of limited help in our series.